PERAN MEDIA SOSIAL SEBAGAI SARANA INFORMASI SEKOLAH - Henita; Agus Setiawan; Rama Wijaya Abdul Rozak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to examine the role of school social media as a means of accurate, reliable, and useful information, digital marketing strategies for educational institutions, challenges and solutions in using ICT (Information and Communication Technology) for promotion, and examples of the use of social media as a tool for educational promotion. The study was conducted on December 16-20, 2024 using a quantitative descriptive method. Data were collected through a Google form distributed to parents of students from various levels of education. The results of the study indicate that social media has an important role in supporting communication and engagement between schools and the community. As many as 83.28% of respondents agreed that school social media provides accurate and reliable information. Digital marketing strategies, such as school advertising through online platforms, were also considered effective, with 78.95% of respondents stating that digital advertising helped understand school programs. Challenges in the use of ICT, such as regular content updates and limited infrastructure, are concerns, but solutions in the form of training and technological improvements can help overcome them. As many as 84.14% of respondents agreed that social media is an effective tool for promoting educational institutions, through WhatsApp, Instagram, YouTube, and Facebook as popular platforms. In conclusion, social media not only supports the delivery of accurate, reliable, and useful information, but also strengthens the relationship between schools and communities and increases parental involvement in the educational process. To maximize these benefits, special attention is needed to the challenges faced, such as the development of technological infrastructure and increasing digital literacy. By overcoming these obstacles, the use of social media and ICT can be more optimal in the future, making a significant contribution to the advancement of the world of education.